Knowledge, Attitude and Practice Towards Domestic Solid Waste Management in Rural District, Bac Lieu Province, Vietnam - Nguyen Thanh Giao; Tran Tu Thien (Indonesian Journal of Environmental Management and Sustainability, 2022)
The characteristics of waste composition and community behavior are important data for making an appropriate domestic solid waste management plan. However, these data are lacking or not studied in Bac Lieu, especially in rural areas. Therefore, the study was conducted to determine the domestic waste composition and evaluate the factors related to the knowledge, attitude and practice (KAP) level of the community in domestic solid waste management in Phuoc Long district, Bac Lieu province, Vietnam. The results of domestic solid waste samples collected at households showed that the waste was composed of organic (73.8%), recyclables (15.7%), hazardous waste (0.7%), and others (9.9%). Plastic bags (42.7%) and papers (30.5%) were predominant in the recyclables. The interview of 150 households indicated that the majority of respondents had an average level of knowledge (46%), and attitude (49.3%). However, 46% of respondents had an inadequate level of practice. In addition, the study observed that respondents have a good level of knowledge and attitude that leads to good practice. The Chi-square test showed that the KAP level of the respondents is influenced by demographic factors including age, education, occupation and income (p<0.05). In which, education level and age were the significant influencing factors. The results indicated that education for improving the community’s knowledge and attitudes in domestic solid management should pay more attention on the population aged over 60 years and those with occupations belonging to agriculture and housework.